Hydrothermal treatment with VO2(B) nanobelts for synthesis of VO2(A) and W doped VO2(M) nanobelts. (April 2015) - Zhang, Y.; Tan, X.; Huang, C.; Meng, C.
Abstract : In this paper, the conversion of VO2 (B) nanobelts under the hydrothermal condition in the absence/presence of dopant was studied. The synthetic conditions, such as the reaction temperature, reaction time, quantity of the dopants and kinds of dopants, were briefly discussed to prepare VO2 (A) and W doped VO2 (M) solid solution. It was found that the dopant played a crucial role in controlling VO2 polymorph, and the results showed that VO2 (A) was obtained in the absence of dopant, whereas W doped VO2 (M) was obtained in the presence of tungstenic acid. The transformation mechanism from VO2 (B) to VO2 (A) and W doped VO2 (M) was discussed in detail. The phase transition temperature ( T c ) of VO2 (A) and W doped VO2 (M) was evaluated by differential scanning calorimetry. It is found that doped atoms can be successfully doped into the crystal lattice of VO2 (M) matrix, and the T c of W doped VO2 (M) can be reduced by W doping. The optical switching properties were studied by the variable temperature infrared spectra, and it was found that the as obtained VO2 (A) and W doped VO2 (M) had outstanding thermochromic characters and optical switching properties.